THE INVESTIGATION OF THE ROLE OF TRANSFORMATIONAL LEADERSHIP AND SELF-EFFICACY ON JOB PERFORMANCE EMPLOYEES: EMPIRICAL STUDY - Adesti, Shakti Putri Pratama Mulya; Herachwati, Nuri; Nadia, Fiona Niska Dinda; Muzakki, Muzakki (Fokus Ekonomi : Jurnal Ilmiah Ekonomi, 2023)
Companies most likely give a great deal of attention to workers' performance, as they should be doing. Employees need to be taken into consideration since they are highly crucial to building productivity and profitability, which, in turn, may have repercussions for the success of a business. However, these results will only occur with excellent performance from employees. This research was conducted to know whether self-efficacy and transformational leadership partially or simultaneously affect job performance. Participants in this study were randomly selected from PT. Panca Mitra Multiprima. In this research project, a random sampling approach was used to collect data, and 128 samples were obtained. Meanwhile, we used a questionnaire that had previously been tested for validity and reliability for data collection purposes. In this study, multiple linear regression analysis was the method of choice for data mining. According to research findings, transformational leadership and self-efficacy have an excellent effect on work performance, but only transformational leadership is significant. Self-efficacy, on the other hand, is not significant. In addition, the two different aspects of work performance simultaneously have a good and substantial influence.